2015
DOI: 10.1002/nau.22877
|View full text |Cite
|
Sign up to set email alerts
|

Use of preoperative factors including urodynamic evaluations and nerve‐sparing status for predicting urinary continence recovery after robot‐assisted radical prostatectomy: Nerve‐sparing technique contributes to the reduction of postprostatectomy incontinence

Abstract: Preoperative factors, including the results of UDS, could not predict continence 1 year after RARP. The NS procedure contributed to continence status. NS favorably affected MUCP and FUL; however, it did not affect bladder function after RARP. Neurourol. Urodynam. 35:1034-1039, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
3
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 27 publications
7
71
3
9
Order By: Relevance
“…A total of 1738 patients (780 RRP, 937 RARP, and 21 laparoscopies [LP]) were included in the four studies reporting the hazard ratio for the recovery of continence [20,22,24,26]. For the study reporting the OR of a return to continence at 1 mo, a total of 872 patients (416 RRP and 456 RARP) were included [18], for the studies at 3 mo 2517 patients (571 RRP, 1697 RARP, and 249 LP) were included [14,19,21,22,25,26], at 6 mo 3187 patients (1667 RRP, 589 RARP, and 931 LP) were included [14,16,26], and at 12 mo 4656 patients (2555 RRP, 998 RARP, and 1103 LP) were included [1518,23,26]. …”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1738 patients (780 RRP, 937 RARP, and 21 laparoscopies [LP]) were included in the four studies reporting the hazard ratio for the recovery of continence [20,22,24,26]. For the study reporting the OR of a return to continence at 1 mo, a total of 872 patients (416 RRP and 456 RARP) were included [18], for the studies at 3 mo 2517 patients (571 RRP, 1697 RARP, and 249 LP) were included [14,19,21,22,25,26], at 6 mo 3187 patients (1667 RRP, 589 RARP, and 931 LP) were included [14,16,26], and at 12 mo 4656 patients (2555 RRP, 998 RARP, and 1103 LP) were included [1518,23,26]. …”
Section: Evidence Synthesismentioning
confidence: 99%
“…MRI examinations were performed with the patient positioned in the supine position using 1.5T or 3T MRI units acquiring T2-weighted images which were used for MUL measurements. The use of an endorectal coil was used in four studies [16,21,24,26], not used in four studies [14,22,23,25], and not reported in five studies [15,1720]. MUL was measured in either: (1) the coronal plane in six studies [16,1921,25,26], (2) the sagittal plane in three studies [14,17,22], (3) the sagittal plane cross-referenced with the coronal plane in two studies [23,24], and (4) not reported in two studies [15,18].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…This has been physiologically shown by Nelson et al [18] who measured changes in the intraurethral pressure caused by intraoperative NVB stimulation and noted an increase in pressure on NVB stimulation. Kadono et al [19] performed urodynamic measurements pre-op, immediately after op, and 1 year after RARP and demonstrated that recovery patterns of storage and voiding functions were the same among non-NVB, unilateral-NVB, and bilateral NVB groups and that higher degrees of NVB preservation contributed to lesser decreases in MUCP and longer functional urethral length (FUL) after RARP.…”
Section: Surgical Techniques To Optimize Urinary Continencementioning
confidence: 99%